Association Between Physical Activity Dose and Mental Health Among Stroke Survivors - Ajith Kumar Vemuri; Seyyed Sina Hejazian; Alireza Vafaei Sadr; Aishwarya Chandrasekaran; Sasan Bahrami; Shouhao Zhou; Jonathan Hakun; Christopher Sciamanna; Vida Abedi; Ramin Zand (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Although physical activity correlates with reduced depressive symptoms among survivors of stroke, how frequency, intensity, and duration of physical activity relate to mental health is unknown. This study aims to find the association of physical activity doses recommended in 2011, 2014, and 2021 American Heart Association/American Stroke Association guidelines with mental health burden (number of days of poor mental health). Analysis was expanded to find the optimal dose linked to mental health burden. Methods We used data from the 2011 to 2019 Behavioral Risk Factor Surveillance System, a nationally representative survey. The mental health burden between guideline‐adherent and nonadherent groups was compared. Propensity score matching was used to balance the 2 groups with respect to sociodemographic factors and comorbidities. The relative difference in mental health burden between the groups is reported. The impact of duration, frequency, and intensity was analyzed using nonlinear regression, adjusting for potential confounders. We further performed a comparative analysis among survivors of myocardial infarction. Results Survivors of stroke who adhered to 2011, 2014, and 2021 guidelines had 0.6, 0.8, and 0.3 fewer days of poor mental health, with relative differences of 11.1%, 14.8%, and 5.8%, respectively. Among survivors of stroke adhering to 2014 guidelines (3–4 sessions/week, 40 minutes/session), younger (18–64) individuals showed greater relative differences in mental health burden at 15.7%. For those adhering to 2021 guidelines (4 moderate 10‐minute or 2 vigorous 20‐minute sessions), older (≥65) individuals had higher relative differences at 11.1%. Regression analysis showed that the optimal dose is 4 to 6 weekly sessions of moderate physical activity, each lasting 45 minutes. Conclusions The findings suggest that physical activity doses recommended in 2011, 2014, and 2021 American Heart Association/American Stroke Association guidelines are associated with lower mental health burden. Furthermore, the amount of physical activity associated with lower mental health may vary by subpopulations (eg, age). Randomized control trials are needed to validate the optimal dose.